MANAJEMEN PENGELOLAAN LAYANAN ASKES PENYAKIT SPESIFIK DENGAN KONSEP DESING DFD LEVEL 2 MENGGUNAKAN CMD - Choirul, A’an; Firda, Alifia; Fauzi, dkk, Ahmad (DINAMIKA DOTCOM, 2019)
Along with the development of the times, technological developments also developed. One of them in the health sector such as the hospital administration of information and communication technology is always required to develop in accordance with the progress of the times. The purpose of writing this journal, to provide information about the Data Base Health Insurance focused on claims for Specific Diseases. This journal contains methods and results from the data base. Claim flow so participants can get their rights. Thus it can be concluded that there are several that can be used for the system, namely making DFD and ERD. Keywords : information system, specific data base for disease claims